Cross Sectional Survey of Canine Idiopathic Epilepsy Management in Primary Care in the United Kingdom - Griffin, Sebastian; Stabile, Fabio; De Risio, Luisa (Frontiers in Veterinary Science, 2022)
The aims of this study are to gain insight on how primary care veterinarians in the UK diagnose and treat canine idiopathic epilepsy (IE) and what they perceive as challenges in the management of canine IE. Two hundred and thirty-five primary care veterinarians took part in this survey. The questionnaire asked about the type of practice the respondent worked in, any relevant post-graduate qualifications, how many years’ experience they had in practice and the participant’s canine IE caseload. Participants were asked how they diagnose canine IE, how they select antiseizure drugs (ASDs) and how they assess outcome. The questionnaire also explored which information sources they have access to for deciding on canine IE treatment, challenges that may be faced when managing these cases and areas in which more support can be provided. 94.5% of participants (n=222/235) managed less than 10 canine IE cases in a year and 87.8% (n=206/235) used phenobarbital as their first line ASD. The reported mean initial phenobarbital dose was 2.1mg/kg (standard deviation=0.71) every 12 hours. When considering how closely participants aligned with IVETF guidelines on the topics of diagnosis, ASD initiation and outcome assessment, on average participants would score around half of the available points. 53.2% (n=125/235) of respondents recommended neutering in canine IE and 46.8% (n=110/235) did not. 53.2% (n=125/235) did not recommend any additional treatments for canine IE beyond use of ASDs. 23.4% recommended Purina Neurocare diet (n= 55/235), 12.8% recommended environmental modification (n=30/235), and 6.8% (n=16/235) recommend medium chain triglyceride supplements. In this study participants found managing client expectations to be most challenging alongside canine IE emergency management. The main limitation of this study is the relatively low response rate and therefore the results may not reflect the entire small animal veterinary profession in the UK. However, the results of this study represent a starting point to inform educational resources and support strategies to improve quality care of canine IE in primary care.